2013
DOI: 10.1080/00288306.2013.772906
|View full text |Cite
|
Sign up to set email alerts
|

Quaternary shelf structures SE of the South Island, imaged by high-resolution seismic profiling

Abstract: Along the south-eastern coast of New Zealand's South Island, observations and characterisations of shelf geology are complicated by numerous possibly active faults (e.g. the coast-parallel Akatore and coast-perpendicular Waihemo and Castle Hill faults), a Miocene-aged volcanic edifice (i.e. the Dunedin volcano) and incision from an extensive submarine canyon system. Conventional marine seismic data do not adequately image the basin beneath the shallow shelf here. However, six recently digitised high-frequency … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…Based on previous studies of the dive behaviour of yellow-eyed penguins, which demonstrated a consistent and specialised benthic foraging strategy (e.g., Mattern et al, 2007), we hypothesised that seafloor depth would have a major influence on yellow-eyed penguin marine space use. Although their eastward dispersal from the coast is bounded by the continental shelf and the shelf break, which occurs at approximate depths of 125-150 m (Carter et al, 1985;Sutton, 2003;Gorman et al, 2013;Stevens et al, 2019), bathymetry had low importance in most of the models. This is also contrary to previous baseline spatial modelling showed its significance to regional habitat suitability (Mattern, 2020).…”
Section: Environmental Predictorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on previous studies of the dive behaviour of yellow-eyed penguins, which demonstrated a consistent and specialised benthic foraging strategy (e.g., Mattern et al, 2007), we hypothesised that seafloor depth would have a major influence on yellow-eyed penguin marine space use. Although their eastward dispersal from the coast is bounded by the continental shelf and the shelf break, which occurs at approximate depths of 125-150 m (Carter et al, 1985;Sutton, 2003;Gorman et al, 2013;Stevens et al, 2019), bathymetry had low importance in most of the models. This is also contrary to previous baseline spatial modelling showed its significance to regional habitat suitability (Mattern, 2020).…”
Section: Environmental Predictorsmentioning
confidence: 99%
“…Productive regions around current systems and frontal zones are important areas for many pelagic foraging seabird and penguin species (Hull et al, 1997;Boersma and Rebstock, 2009;Bost et al, 2009;Mattern et al, 2018b). In New Zealand, the northward flowing Southland Current is bounded by the Subtropical Front where Subtropical and Subantarctic waters meet (Gorman et al, 2013;Stevens et al, 2019;Stephenson et al, 2020). These currents and fronts extend to the seafloor during parts of the year due to the shallow (<150m) continental shelf around the South Island (Hopkins et al, 2010;Stevens et al, 2019), which could directly influence benthic foraging yellow-eyed penguins.…”
Section: Introductionmentioning
confidence: 99%
“…PML is a coastal station situated within the semi-enclosed Otago Harbor which has a mean depth of 4.5 m and is located on the southeast coastline of the South Island, New Zealand (Otago Regional Council and Dunedin City Council, 1991). PML is located 8 km from the entrance and 25 km inshore of the continental shelf break (Gorman et al, 2013). Circulation on the surrounding shelf is affected by an equatorward flowing WBC, known locally as the Southland Current (Sutton, 2003), which transports a combination of warmer subtropical shelf-water and cooler offshore subantarctic waters northeastward.…”
Section: Introductionmentioning
confidence: 99%